Raspberry Pi with Java programming the internet of things (IoT) - Chin, Stephen 1977-; Weaver, James L. (McGraw-Hill Education, 2016)
Use Raspberry Pi with Java to create innovative devices that power the internet of things! Raspberry Pi with Java: Programming the Internet of Things (IoT) fills an important gap in knowledge between seasoned Java developers and embedded-hardware gurus, taking a project-based approach to skills development from which both hobbyists and professionals can learn. By starting with simple projects based on open-source libraries such as Pi4J, hobbyists can get immediate results without a significant investment in time or hardware. Later projects target simplified industrial use cases where professionals can start to apply their skills to practical problems in the fields of home automation, healthcare, and robotics. This progression prepares you to be an active participant in the IoT revolution that is reshaping our lives. For the hobbyist: Hardware used in projects is affordable and easily accessible Follows a project-based learning approach with a gradual learning curve Projects are based on open-source code repositories with commercial friendly licenses For the professional computer engineer: Uses an industry-standard platform that allows for high performance, secure, production-ready applications Introduces Java SE Embedded for large devices and Java ME Embedded for small devices Code is portable to a wide variety of ARM and MIPS based platforms Provides practical skill development with advanced projects in the fields of home automation, healthcare, and robotics.